PERSONAL SELLING, ADVERTISING dan ASURANSI (Studi Pada PT. Prudential Life Assurance Cabang Pandanaran Semarang) - Dinda Indriana Hapsari; Heru Eko Prasetyo (FEB UNTAG Semarang, 2019)
This study aims to determine how the influence of personal selling and advertising on purchasing decisions for insurance products at PT. Prudential Life Assurance, Pandanaran Semarang Branch.The population in this study are all customers who use insurance products PT. Prudential Life Assurance Pandanaran Semarang Branch, with a sample size of 70 respondents. The sampling technique used is simple random sampling. The data source used is primary data, with data collection techniques using questionnaires, while the data analysis technique used is multiple linear regression.The research results seen from the equation of multiple linear regression analysis shows that personal selling and advertising have a positive effect on purchasing decisions. The coefficient of determination shows that personal selling and advertising variables can explain the variation in the purchase decision variable by 60.3%. The results of the hypothesis test using the t test statistic indicate that personal selling has a positive and significant effect on purchasing decisions, and advertising has a positive and significant effect on purchasing decisions.Keywords: Personal Selling, Advertising, and Purchasing Decisions.